19(3x-6)=25(x+2)

Simple and best practice solution for 19(3x-6)=25(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19(3x-6)=25(x+2) equation:


Simplifying
19(3x + -6) = 25(x + 2)

Reorder the terms:
19(-6 + 3x) = 25(x + 2)
(-6 * 19 + 3x * 19) = 25(x + 2)
(-114 + 57x) = 25(x + 2)

Reorder the terms:
-114 + 57x = 25(2 + x)
-114 + 57x = (2 * 25 + x * 25)
-114 + 57x = (50 + 25x)

Solving
-114 + 57x = 50 + 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
-114 + 57x + -25x = 50 + 25x + -25x

Combine like terms: 57x + -25x = 32x
-114 + 32x = 50 + 25x + -25x

Combine like terms: 25x + -25x = 0
-114 + 32x = 50 + 0
-114 + 32x = 50

Add '114' to each side of the equation.
-114 + 114 + 32x = 50 + 114

Combine like terms: -114 + 114 = 0
0 + 32x = 50 + 114
32x = 50 + 114

Combine like terms: 50 + 114 = 164
32x = 164

Divide each side by '32'.
x = 5.125

Simplifying
x = 5.125

See similar equations:

| -9h=-10h+10 | | 4r^2-16r-128= | | 125=8-3x | | 1.9=1.9-0.9x | | x/7-5=-11 | | -6m=-8-8m | | 6x+3x-5=49 | | -8r=10+2r | | 12x-20y=12 | | (2+3i)(x-iy)=3(x-2iy)+(2+i) | | -5+8x=2(14x+10)-x | | v+7=v | | -12x+7=-5 | | 9j-10=8j | | 14x+28-10x=8 | | (v^7)(v^2)= | | Tanx=0.44469726 | | 3+7x=2(4x+(-5))+x | | -3g+5=-3g | | 9-7x=7-4 | | X+6=3(5x-4) | | 90/4x3 | | X+32.7=-5.1 | | -9+10p=9p | | x/5-9=8 | | 3(x+5)=9(x+1) | | 2y-7-5y=-17 | | 2x+4=28+5x | | -9x+8=-19 | | 7x+1=8x+17 | | -9x-8=-19 | | (-7/3)x-3=-52 |

Equations solver categories